The system of leading indicators for Ukrainian construction companies - Moholivets, А. (Ways to Improve Construction Efficiency, 2018)
The main predictors of the phase change of the economic cycle for construction are analyzed. The following indicators are proposed: the growth rate of consumer confidence, the growth rate of entrepreneurial confidence, the growth rate of real GDP, the growth of consumer spending, fixed capital, stocks, unemployment, the ratio of growth in labor productivity to the growth rate of wages, inflation, lending rate, interest on deposit, the growth rate of lending to the population, the growth rate of loans to construction enterprises, the growth rate of construction work. The possibility and expediency of realization of anticyclic management of financial stability of construction enterprises with the help of these factors is proved.